2012
DOI: 10.1016/j.autneu.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental gestational hypothyroidism evokes hypertension in adult offspring rats

Abstract: Gestational hypothyroidism is a prevalent disorder in pregnant women. We aimed to investigate the impact of experimental gestational hypothyroidism (EGH) on cardiovascular and autonomic nervous systems (ANS) in the offspring of rats. EGH was induced with methimazole (MMI) 0.02% in drinking water from day 9 of gestation until birth. Sixty day old offspring from MMI-treated dams (OMTD, n=13) or water-treated dams (OWTD, n=13) had femoral arteries surgically assessed for the measurements of heart rate (HR), mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
(64 reference statements)
2
18
1
Order By: Relevance
“…All values are means ± SEM; n = 10; repeated measure ANOVA followed by Bonferroni test was used for comparing between groups; all * p < 0.05, † p < 0.01, ‡ p < 0.001 vs. control. Contrary to the above mentioned results, Santos et al (2012) report that FH induces hypertension. Although the reason for this discrepancy is not exactly clear, explanations include difference in types of antithyroid drugs used (PTU vs. methimazole), time of drug administration during pregnancy (first day of conception until delivery vs. day 9 until delivery), and age of rats at time of BP measurement (~ 95 days vs. 60 days).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…All values are means ± SEM; n = 10; repeated measure ANOVA followed by Bonferroni test was used for comparing between groups; all * p < 0.05, † p < 0.01, ‡ p < 0.001 vs. control. Contrary to the above mentioned results, Santos et al (2012) report that FH induces hypertension. Although the reason for this discrepancy is not exactly clear, explanations include difference in types of antithyroid drugs used (PTU vs. methimazole), time of drug administration during pregnancy (first day of conception until delivery vs. day 9 until delivery), and age of rats at time of BP measurement (~ 95 days vs. 60 days).…”
Section: Discussioncontrasting
confidence: 50%
“…The sex-associated differences in blood pressure, observed in humans, have also been documented in animal models (Reckelhoff 2001). Finally, outcomes of impaired intrauterine growth may vary according to age of offspring ( Roland et al 2010;Karbalaei et al 2013), results that justify both ours and those of Santos et al (2012).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Experimental studies have shown that an adequate maternal thyroid function during gestation was necessary for the proper expression of both structural and regulatory genes in cardiomyocytes of foetal rats . Also, experimental gestational hypothyroidism in rats increased systolic and diastolic blood pressure in adult offspring . Maternal hyperthyroidism was associated with altered expression of renin‐angiotensin system components in rat pups .…”
Section: Introductionmentioning
confidence: 94%
“…Small size for gestational age children have higher risks of infant catch‐up growth and an adverse cardiovascular profile in later life . Thus far, it is not known whether first‐trimester maternal thyroid hormone levels affect childhood growth and cardiovascular development . Experimental studies have shown that an adequate maternal thyroid function during gestation was necessary for the proper expression of both structural and regulatory genes in cardiomyocytes of foetal rats .…”
Section: Introductionmentioning
confidence: 99%